The seniority structure of sovereign debt - Matthias Schlegl; Christoph Trebesch; Mark L. J. Wright (Kiel Institute for the World Economy (IfW), 2019)
Sovereign governments owe debt to many foreign creditors and can choose which creditors to favor when making payments. This paper documents the de facto seniority structure of sovereign debt using new data on defaults (missed payments or arrears) and creditor losses in debt restructuring (haircuts). We overturn conventional wisdom by showing that official bilateral (government-to-government) debt is junior, or at least not senior, to private sovereign debt such as bank loans and bonds. Private creditors are typically paid first and lose less than bilateral official creditors. We confirm that multilateral institutions like the IMF and World Bank are senior creditors.
Keywords: F3; F4; F5; G1; 330; Sovereign default; Arrears; Insolvency; Priority; IMF; Official Debt; Sovereign bonds; International Financial Architecture; Pecking Order